Caregiver-perceived racial discrimination is associated with diverse mental health outcomes in Aboriginal and Torres Strait Islander children aged 7-12 years - Leah Cave; Matthew N. Cooper; Stephen R. Zubrick; Carrington C. J. Shepherd (BMC, 2019)
Abstract Background Racial discrimination is acknowledged as a central social determinant of Australian Aboriginal and Torres Strait Islander (hereafter referred to as Aboriginal) health, although quantitative empirical literature on the impacts of racism on Aboriginal children remains sparse. We use a novel, longitudinal dataset to explore the relationship between caregiver-perceived racism exposure and a range of mental health and related behavioural and physiological outcomes in childhood. Method The study cohort comprised 1759 Aboriginal children aged 4-12 years from waves 2-8 (2009-2015) of the Footprints in Time: The Longitudinal Study of Indigenous Children (LSIC) dataset. We examined exposure to caregiver-perceived racism between 4 and 11 years as a predictor for mental health and related outcomes at ages 7-12 and substance use at 10-12 years. Unadjusted models and models adjusted for remoteness, community-level and family-level socio-economic status, child age and gender were used in analysis. Multilevel logistic regression was used in all analysis. Results In fully adjusted models, perceived exposure to racism at ages 4-11 was associated with twice the risk of negative mental health (95% CI: 1.3-3.0), sleep difficulties (95% CI: 1.4-3.0), and behaviour issues at school (95% CI: 1.2-2.9), 1.7 times the risk of obesity (95% CI: 1.1-2.5), and nearly 7 times the risk of trying cigarettes (95% CI: 1.1-43.9). Increased risks were also found for being underweight and trying alcohol though estimates did not reach statistical significance. There was no evidence that racism was associated with poorer general health. Conclusion Exposure to racial discrimination in Aboriginal children increased the risk for a spectrum of interrelated psychological, behavioural and physiological factors linked to negative mental health. Our results further affirm the importance of interventions aimed at reducing the prevalence of racial discrimination for the benefits of population health and health inequalities. The services and institutions which aim to support the mental health and wellbeing of Aboriginal children should also support interventions to reduce racism and implement accountable policies which prioritise this goal.